Isolation of Indigenous Bacteria of Phosphate Solubilizing from Green Bean Rhizospheres - N Arfarita; M W Lestari; I Murwani; T Higuchi (Brawijaya University, 2017)
The use of phosphate-solubilizing bacteria (PSB) as a biological fertilizer of Agricultural land is one solution to overcome problem of phosphate availability for plants. However, often application of a biological fertilizer is ineffective for certain places. The purpose of this study was to obtain indigenous phosphate solubilizing bacterial isolates that can be effective in the area of Malang. Samples were collected from rhizosphereof green bean plants at three locations in Malang, East Java. The study was conducted to determine the total bacterial population of soil samples, to select the best three bacterial isolates in phosphate solubilizing ability, which is not antagonistic and nonpathogenic for plants,along with observing its potential as a bacterial consortium. The highest total population was found in FHR samples of 1.5x1011 CFU / mL. We have selected three bacterial isolates namely SPP1, SPP2 and SPP3. They were not antagonistic to each other and nonpathogenic on mungbean sprouts. They had possibility of producing growth hormone which characterized by an increasing in length of plant and total root length, be compared to controls. Strain SPP2 has shown the highest activity of phosphate solubilization then was selected for 16S rRNA identification. Similarity test of genome sequence of strain SPP2 had 99% similarity with Pseudomonas plecoglossicida strain PR19